KAJIAN SIFAT FISIK DAN KIMIA JERUK SIAM (Citrus nobilis var. microcarpa) SEMBORO BERDASARKAN UMUR SIMPAN MENGGUNAKAN PENGOLAHAN CITRA DIGITAL - Herman Setiawan; Dedy Wirawan Soedibyo; Dian Purbasari (Universitas Andalas, 2019)
Since hundreds of years ago, orange have grown in Indonesia either naturally or cultivated. One of the most popular places for producing orange varieties is Semboro, Jember Regency. The quality of Semboro oranges is influenced by the level of harvest age and shelf life. In the storage process, Orange expiriences physically and chemical changes at each shelf life which is detrimental. At present the tests performed on Semboro orange are destructive. Based on this, non-destructive measurements are needed by using other methods such as digital image processing. The purpose of this study was to identify the relationship between the physical and chemical properties of Semboro orange based on shelf life. The Semboro Orange used was 150 fruits of super quality with code size 1 and the same picking age of 28 MSB (weeks after flowering). Semboro oranges are stored for 15 days and measured with variations in shelf life of 1, 8 and 15 days. This research was conducted in two stages, namely taking pictures and measuring physical and chemical characteristics. Orange samples were then measured interm of physical and chemical properties using the O'hauss pioneer digital scales, penetrometer, refractometer and pH meter to obtain data on fruit weight, fruit hardness, total dissolved solids and acidity (pH) of the fruit. The value of the image quality variable and the physical and chemical properties were analyzed using one way anova test, correlation, regression, boxplot and validation test.